Severe hepatic-neurological complications of dengue fever in children from a tertiary care center in North India - Pradeep Kumar Sharma; Maneesh Kumar; Ashish Sahani; Rohit Goyal; Girraj K Aggarwal; Virender Kumar (Wolters Kluwer Medknow Publications, 2016)
Objective: To present clinical experience and outcome of severe hepatic-neurological complications of dengue fever. Methods: From August to November 2015, all confirmed dengue cases admitted to Pediatric intensive care unit(PICU) were studied and data was retrospectively collected and analyzed. Results: Out of196 confirmed dengue cases 11 had severe hepatic-neurological complications Neurological complications were seen in 7 patients of which 2 had meningoencephalitis, 2 had meningitis and 3 had seizures. All recovered completely except one who had sequelae. Acute liver failure occurred in 4 and 3 recovered completely except one who expired. Conclusions: Use of N-acetylcysteine in ALF is found to be beneficial. In our experience outcome of these complications is good, however larger trials are needed to investigate further.